PENGARUH METODE TUTOR SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 16 MATARAM TAHUN AJARAN 2019/2020 - Leni Widia Ningsih; Muhammad Turmudzi; A. Witono (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
This study aims to determine the effect of peer methods on mathematics learning outcomes of fourth grade students of SDN 16 Mataram in the academic year 2019/2020. The results of this research are expected to be useful theoretically and practically. This type of research is an experimental study with a quasi experimental design type nonequivalent control group design. The population of this research is all students of class IV SDN 16 Mataram in the academic year 2019/2020 consisting of two classes namely class IV / A and IV / B. Sampling technique This research is a saturated sample ... The data collection methods are observation, test, and documentation. Data analysis was performed with a normality test, a homogeneity test, and a hypothesis test using the formula t-test variance. Based on the posttest results, the average value of mathematics learning outcomes in the experimental class is 76 while the average control class is 51 so the experimental class has a higher average value than the control class. Hypothesis testing at a significant level of 5% yields t-count = 8.821 while t-table = 1.686, in other words, t-count> t-table. Based on the testing criteria, if tcount> ttable, then H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is a positive and significant influence of the use of peer tutoring methods on mathematics learning outcomes of students in grade IV SDN 16 Mataram in the 2019/2020 school year.